2019
DOI: 10.1186/s12966-019-0809-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in body weight and physical activity in relation to all-cause and cardiovascular mortality: the HUNT study

Abstract: Background Most previous studies have relied on single measurements of body weight and physical activity and have not considered the interplay between long-term changes in body weight and physical activity in relation to mortality. The aim of the current study was therefore to examine the joint effect of changes in body weight and leisure-time physical activity over a period of ~ 10 years on all-cause and cardiovascular mortality. Methods The study population comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(35 reference statements)
2
14
0
1
Order By: Relevance
“…This suggests that the health advice provided by our team including physiotherapy students and qualified supervising physiotherapists, appeared to be effective in positively modifying lifestyle behaviours with participants reducing their BMIs and WCs. This is not surprising, as the interaction between PA and BMI is well established [17,18]. Although the changes in BMIs and WCs were relatively small, the improvement in our intervention group was positive and statistically significant.…”
Section: Discussionsupporting
confidence: 62%
“…This suggests that the health advice provided by our team including physiotherapy students and qualified supervising physiotherapists, appeared to be effective in positively modifying lifestyle behaviours with participants reducing their BMIs and WCs. This is not surprising, as the interaction between PA and BMI is well established [17,18]. Although the changes in BMIs and WCs were relatively small, the improvement in our intervention group was positive and statistically significant.…”
Section: Discussionsupporting
confidence: 62%
“…Some studies have suggested that TMAO may be a predictor of CVD risk, since patients with heart failure had higher plasma TMAO levels [120]. However, in the Genoni et al study, no difference in TMAO levels was observed between the Paleolithic diet and the Australian Guide to Healthy Eating diet [119].…”
Section: Low-carbohydrate Dietmentioning
confidence: 88%
“…However, not all Paleolithic diets are rich in n-3, and these results should not be used as an overall influence. Trimethylamine-N-oxide (TMAO) is produced by microbiota due to the consumption of milk, eggs, and meat [119]. Some studies have suggested that TMAO may be a predictor of CVD risk, since patients with heart failure had higher plasma TMAO levels [120].…”
Section: Low-carbohydrate Dietmentioning
confidence: 99%
“…As population samples are heterogeneous and consequently result in heterogeneous findings, validation studies based on small samples may have limited representability. Furthermore, considering that already established longitudinal population cohorts have implemented PAQs from inception allowing for long follow-up time (SGPALS: >45 years,28–30 PAFID: >35 years31), validation of PAQs and sitting questionnaires against accelerometry measured physical activity and sitting time from large heterogeneous samples will allow researchers to more accurately interpret results from longitudinal cohort studies where only questionnaires are the physical activity and sedentary time measure.…”
Section: Introductionmentioning
confidence: 99%